Design of Power-Efficient Structures of the CAM Cell using a New Approach in QCA Nanoelectronics Technology - Ali Hussien Majeed; Ahmed Abdulelah; Mohd Shamian Zainal; Esam Alkaldy (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
Quantum-dot Cellular Automata (QCA) is a new emerging nano-electronic technology. Owing to its many fa-vorable features such as low energy requirements, high speed, and small size, QCA is being actively suggested as a future CMOS replacement by researchers. Many digital circuits have been introduced in QCA technology, most of them aiming to reach the function with optimum construction in terms of area, cell count and power consumption. The memory circuit is the main building block in the digital system therefore the researchers paid attention to design the memory cells with minimum requirements. In this paper, a new methodology is intro-duced to design two forms of CAM cell. The proposed designs required two 2:1 multiplexers, one OR gate and one inverter. The first proposed design reduces the power consumption by 53.3%, 35% and 25.9% at (0.5 Ek, 1 Ek, and 1.5 Ek) while the second design by 53.2%, 31.9% and 20.5% (0.5 Ek, 1 Ek, and 1.5 Ek) respectively.